ANALISA TITIK IMPAS DAN TARGET LABA DALAM PENENTUAN HARGA SEWA PADA JASA SEWA KENDARAAN - Jonathan Lucky Sasmitha (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2018)
This research was conducted to find out how to determine the selling price in the field of vehicle rental services business using break-even point analysis and profit target. Data collection techniques carried out are through documentation. The results of the study based on break-even analysis and profit targets indicate that the rental price set by PT. CTB is calculated using day units for each order from the consumer. Rental prices are calculated by adding up variable costs and fixed costs per day.Break-even points to cover all costs are if there are at least 15 bookings (15 days) in one month. New profits were obtained by PT. CTB if the rental amount exceeds 15 days.